Analyis Of Gear Strenght In Machine Construction - amiko amiko; Yuki Alvandi Pratama; Beny Gusman; Muhamad Adriansyah; Fardin Hasibuan; Eddy Efiano (Universitas Riau Kepulauan, 2026)
Gears are essential components in mechanical transmission systems, responsible for transferring power between shafts in various types of machinery. The strength of gears plays a critical role in the efficiency and reliability of these systems, as improper load handling can lead to material failure or gear damage. This study aims to analyze the strength of gears by considering several factors such as material properties, geometry, and operational conditions. The materials tested in this research include carbon steel SAE 1045, alloy steel SAE 4140, and stainless steel (SS 304), all of which are commonly used in gear applications. The gear geometry analyzed includes variations in module (2 mm and 3 mm), the number of teeth (20 teeth), and the pressure angle (20 degrees). The research methodology includes Finite Element Analysis (FEA) to simulate stress distribution on gears under both dynamic and static loading conditions, along with experimental testing to validate the simulation results. The results show that SAE 4140 alloy steel exhibits superior tensile strength and wear resistance compared to SAE 1045 carbon steel, though at a higher cost. Stainless steel (SS 304) offers excellent corrosion resistance but lower tensile strength, making it less suitable for high-load applications. Additionally, increasing the gear size (3 mm module) reduces stress on the teeth but increases the overall size and weight of the gear. This study provides important insights into material selection and gear design, helping to improve the strength and durability of mechanical transmission systems.